A space for transforming masculinities - Cardona Iglesias, Yesika Maria; Rusell Castro, Yeimi Vanessa; Santiago Fontalvo, Tatiana Patricia; Zurita Barrios, Katterine; Mejía Ramírez, Cristian (Comunicación y Género [Communication and Gender], 2023)
The main content of this research is the emergence of the new masculinities, where 11 young men between 18 and 28 years of age and 7 adults from 28 years and older, located in the Barrio Abajo of the municipality of Tubara in the department of Atlántico in Colombia, are taken as a sample and population. The objective is to know the reality about patriarchy and hegemonic masculinities obtained from their ancestors, in the same way, to tell the changes that these new masculinities have dealt with. The study is qualitative, with a historical-hermeneutic approach and an exploratory type of study, to understand and explain these dynamics.The results of the exploration are based on categories and subcategories obtained from a first observation report. In the category of social constructions, the following subcategories emerge patriarchy and gender relations; in the category of new masculinities, the following subcategories emerge self-care, interpersonal relations and popular knowledge; and finally, in the category of masculine identity, subcategories such as hegemonic masculinities and alternative masculinities emerge. Through these, a list of questions was established to unveil these social constructs of the participants and then analyze the responses through the structured interview technique with a differential approach and participant observation. The results explain how the transition from hegemonic masculinities, surrounded by patriarchy and machismo, inherited from ancestors, is entering the new masculinities with alternative and positive thoughts, without causing disrespect or failing the culture of their descendants.
Keywords: Adults; Social constructions; Youth; New masculinities; gender